1984
DOI: 10.1017/s0813483900008640
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship of Psychiatric Diagnosis to Behavioural Assessment

Abstract: In this article we address the relationship between behavioural assessment and psychiatric diagnosis. We argue that a diagnostic formulation should be made prior to behavioural assessment but consider diagnosis as complementary to traditional behavioural assessment. Implicit in our proposal, is the notion that behavioural practitioners should be thoroughly conversant with the various forms of psychopathology, and be able to identify the signs and symptoms that cluster together to constitute a clinical syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The findings support the suggestion that social cognitive factors may have important implications for the assessment process (Wills, 1978). If practitioners include psychiatric diagnoses as part of their assessments, as recommended by Jackson and Tierney (1984), and they do not actively process the information that leads to the diagnostic decision, they should be aware of potential biases in their perceptions of clients. These biases may subsequently affect their interactions.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The findings support the suggestion that social cognitive factors may have important implications for the assessment process (Wills, 1978). If practitioners include psychiatric diagnoses as part of their assessments, as recommended by Jackson and Tierney (1984), and they do not actively process the information that leads to the diagnostic decision, they should be aware of potential biases in their perceptions of clients. These biases may subsequently affect their interactions.…”
Section: Discussionsupporting
confidence: 70%
“…Recently, Jackson and Tierney (1984) urged behavioural practitioners to incorporate psychiatric diagnoses into their assessments. They suggested that the diagnostic process encourages a more complete functional analysis.…”
mentioning
confidence: 99%